Twitter power 3.0 : how to dominate your market one tweet at a time - Comm, Joel.; Taylor, Dave, 1962-; Comm, Joel. (Hoboken, New Jersey : Wiley, 2015)
'Tweet your company to the top of the market with a tailored approach to TwitterTwitter Power 3.0 is the newly updated guide that shows smart businesses and entrepreneurs how to use Twitter to their advantage. This book is the best business leader's guide to Twitter, with the most up to date information on trends in social media, branding, and competitive research. Readers will learn that viral content doesn't happen by accident, why videos and photos are crucial to engagement, and how to measure the success of a Twitter strategy using specific and accurate metrics. This new edition contains brand new case studies, user profiles, features, and images, helping readers create a stronger overall Twitter strategy whether they're already engaged or just wondering if Twitter's important for their business future. Tip: it most definitely is important!Twitter has grown up. It's now a public company, worth over $30 billion, and it means business. Twitter has changed over time, but remains a crucial tool for business branding and a key place to engage with customers and build long-term client relationships. This book demonstrates how Twitter can play an important role in business growth, 140 characters at a time. Understand how Twitter differs from other social media platforms Build a savvy Twitter strategy as part of a broader social media plan Create viral content that effortlessly spreads your message and gains you huge numbers of followers Learn which metrics matter, and how to measure and track them Firms need to understand how Twitter is a vital element in any social media marketing, and craft strategies specific to each. Twitter Power 3.0 is the complete guide to Twitter for business, with the latest information, proven techniques, and expert advice'--
Revision of the author's Twitter power 2.0.
Includes index.
Keywords: Twitter; Internet marketing; Business communication; Online social networks